6701/100 rút gọn là
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(1+\dfrac{100}{20}\right)\) x \(\dfrac{125}{60}\)
\(=6\) x \(\dfrac{125}{60}\)
\(=\dfrac{750}{60}=\dfrac{25}{2}\)
\(\dfrac{4}{100}=\dfrac{1}{25};\dfrac{22}{25}=\dfrac{22}{25};\dfrac{19}{20}=\dfrac{19}{20}\)
\(A=1+3+3^2+3^3+...+3^{99}+3^{100}\\ \Rightarrow3A=3+3^2+3^3+...+3^{100}+3^{101}\\ \Rightarrow3A-A=3^{101}-1\\ \Rightarrow2A=3^{101}-1\\ \Rightarrow A=\left(3^{101}-1\right).\dfrac{1}{2}\\ \Rightarrow\dfrac{3^{101}}{2}-\dfrac{1}{2}.\)
\(A=1+3+3^2+3^3+...+3^{99}+3^{100}\)
Ta có: \(3A=3+3^2+3^3+...+3^{99}+3^{100}\)
Khi đó: \(3A-A=3+3^2+3^3+...+3^{99}+3^{100}+3^{101}-\left(1+3+3^2+3^3+...+3^{99}+3^{100}\right)\)
\(=3^{101}-1\)
\(\Leftrightarrow2A=3^{101}-1\)
Vậy \(A=\left(3^{101}-1\right):2\)
TL ;
\(\frac{6701}{100}\)\(=67,01\)
\(HT\)
67,01 nha